Novel nitric oxide‒generating platform using manuka honey as an anti‐biofilm strategy in chronic rhinosinusitis. Issue 2 (13th December 2019) - Yang, Catherina; Mavelli, Girish Vallerinteavide; Nacharaju, Parimala; Li, Kevin; Cleare, Levi G.; Nosanchuk, Joshua D.; Friedman, Joel M.; Abuzeid, Waleed M.
Abstract : Background: Bacterial biofilms are implicated in the pathogenesis of chronic rhinosinusitis. Nitric oxide (NO) is a key immune effector with potent antimicrobial effects, but a short half‐life limits achievement of therapeutic concentrations. We hypothesized that manuka honey (MH) could induce sustained reduction of nitrite to NO causing biofilm disruption and that this effect would be enhanced with the addition of a NO‐releasing microparticle. Methods: Porous organosilica microparticles containing nitrosylated thiol groups were formulated (SNO‐MP). MH was combined with serial dilutions of nitrite. NO release was evaluated using a NO analyzer. The susceptibility of 2 strains of Pseudomonas aeruginosa biofilms to these NO‐releasing platforms was evaluated using confocal microscopy. Cell viability and biofilm volume were quantified. Statistical analysis was performed using the Mann‐Whitney U test with SPSS software. Results: MH with nitrite generated a linear increase in NO formation. SNO‐MP induced a bolus release of NO within 5 minutes, followed by a sustained plateau phase. MH with nitrite combined with SNO‐MP enhanced NO release during the plateau phase. MH with nitrite reduced biofilm live cells and volume by 88.5% to 96.9% and 95.1% to 95.6%, respectively, vs control ( p < 0.0001). SNO‐MP reduced live cells and volume by 61.0% to 98.5% and 74.7% to 85.7%, respectively, vs control ( p < 0.0001). MH with nitrite combined with SNO‐MP nearly eradicated biofilm, with a 98.3% to 99.8% (log 1.8‐2.6) reduction in viability and a 91.4% to 97.7% decrease in volume ( p < 0.0001 vs control). Conclusion: A novel platform that generates NO using MH and nitrite produces a potent anti‐biofilm effect, which can be further enhanced with the addition of SNO‐MP.